3D reconstruction of geological structures based on remote sensing data: example from Anaran anticline (Lurestan province, Zagros fold and thrust belt, Iran) - Snidero, M.; Amilibia, A.; Gratacos, O.; Muñoz, J. A. (TRABAJOS DE GEOLOGÍA, 2010)
This work describes a methodological workflow for the 3D reconstruction of geological surfaces,exclusively based on satellite data and regional-scale maps. A combined processing of Aster andSPOT images with a digital elevation model has been carried out in order to generate consistent 3Dimages on which our study is based. The structural data have been acquired by means of the 3D digitalmapping. Applying the dip-domain methodology combined with the Discrete SmoothInterpolation (DSI) algorithm, the top surfaces of the Asmari and Ilam formations have been reconstructedalong the southern Anaran anticline (Zagros fold and thrust belt mountain front). The reconstructedsurface geometry allows us to classify the anticline as a fault propagation fold, clearly affectedby a minor back-thrust.